Dose Tolerance Study of Diosmin Against 7 12 Dimethylbenz a Anthracene DMBA Induced Hamster Buccal Pouch Carcinogenesis - Suresh, K (International Journal of Pharmaceutical & Biological Archive, 2014)
Dose Tolerance Study of Diosmin Against 7 12 Dimethylbenz a Anthracene DMBA Induced Hamster Buccal Pouch Carcinogenesis